Exploring the interplay of information relevance and colorfulness in multimedia learning - Désiron, Juliette C.; Schneider, Sascha (Frontiers in Psychology, 2024)
Looking at recent developments in multimedia learning research, the interaction between cognitive and affective processes is examined more extensively. Based on the emotional design hypothesis, for example, using colors, in contrast to black and white representations, for designing learning materials can elicit positive emotions, guide attention, increase motivation, and foster learning. The attention-guiding effect of colors might not be beneficial when used in learning-irrelevant, decorative pictures. In such a case, the seductive detail effect suggests that interesting but irrelevant additions can hinder learning. Previous studies manipulated colors in the whole learning material independent of the relevance of the information. The present study aimed to examine the effect of color variations according to the relevance of the information presented. With a 2 (colorfulness of learning-relevant information background: black and white vs. colored) × 2 (colorfulness of learning-irrelevant pictorial information: black/white vs. colored) between-subject design. The main and interaction effects of colors as attention guides of multimedia learning material on the formation of hurricanes were tested with two samples (128 university students and 140 secondary school students). The first sample is university students in laboratory conditions. The second sample is students in school classes. Besides learning outcomes, perceptions of cognitive load, metacognitive judgments, and affective states are measured. Results show that the interplay between information relevance and the colorfulness of representations affects learners’ cognitive processes and metacognitive and affective perceptions. These findings have practical implications for the design of multimedia learning materials, highlighting the importance of considering the interplay between colorfulness and information relevance.